GAYA BAHASA PERBANDINGAN DALAM NOVEL KARYA OKKY MADASARI - Suci Indah Sari; Yulia Sri Hartati; Ria Satini (Jurnal Inovasi Penelitian, 2021)
This research is motivated by the existence of several styles of comparative attitude contained in the novel by Okky Madasari. This research is focused on the comparative language style in the novel by Okky Madasari. The purpose of this study is to describe the comparative language style in the novel by Okky Madasari. This type of research is qualitative research. The method used in this research is descriptive analysis method. The data in this study are in the form of words, sentences and dialogues related to describing the comparative language style in the novel by Okky Madasari. The data source in this research is the novel by Okky Madasari. The results of this study indicate that the comparative language styles contained in the novel by Okky Madasari are, parable comparison language style, metaphor comparison language style, personification comparison language style, allagory comparison language style, and pleonasm comparison language style. The language style that is most often found is the comparative language style of parable types, and from the research results it is known that of the 10 types of language language there are only 5 types of comparative language styles found.